Characterization and Hepatoprotections of Ganoderma lucidum Polysaccharides against Multiple Organ Dysfunction Syndrome in Mice. (3rd February 2021) - Zhang, Yiwen; Feng, Yanbo; Wang, Wenshuai; Jia, Le; Zhang, Jianjun
Abstract : Background . The liver is one of the most commonly affected organs in multiple organ dysfunction syndrome (MODS). In recent years, there have been many studies on Ganoderma lucidum polysaccharides (GLP), but the role of GLP in MODS is still unclear. The purpose of this work was to explore the antioxidant, anti-inflammatory, and protective effects of GLP on the liver in MODS model mice. Methods . The characteristic properties of GLP were processed by physicochemical analysis. The MODS models were successfully established with intraperitoneal injection of zymosan in Kunming strain mice. The antioxidant, anti-inflammatory, and hepatoprotective effects of GLP were processed both in vitro and in vivo by evaluating the oxidative parameters, inflammatory factors, and liver pathological observations. Results . The characterization analysis revealed that GLP was a pyranose mainly composed of glucose with the molecular weights (Mw) of 8309 Da. The experimental results proved that GLP had potential hepatoprotection possibly by improving the antioxidant status (scavenging excessive oxygen radicals, increasing the antioxidant enzyme activities, and reducing the lipid peroxide), alleviating the inflammatory response (reducing the inflammatory factor levels), and guaranteeing the liver functions. Conclusions . This research suggested that GLP had the potential to be developed as a natural medicine for the treatment of multiple organ failure.